Construction of a circular RNA–microRNA–messenger RNA regulatory network of hsa_circ_0043256 in lung cancer by integrated analysis - Yongwen Li; Ruifeng Shi; Guangsheng Zhu; Chen Chen; Hua Huang; Min Gao; Songlin Xu; Peijun Cao; Zihe Zhang; Di Wu; Xuanguang Li; Hongyu Liu; et al. (Thoracic Cancer, 2022)
Abstract Background Patients with non‐small cell lung cancer (NSCLC) are diagnosed in advanced stages and with a poor 5‐year survival rate. There is a critical need to identify novel biomarkers to improve the therapy and overall prognosis of this disease. Methods Differentially expressed genes (DEGs) were identified from three profiles of GSE101586, GSE101684 and GSE112214 using Venn diagrams. hsa_circ_0043256 were validated using quantitative real‐time polymerase chain reaction (RT‐qPCR). The circular RNA–microRNA–messenger RNA (circRNA–miRNA–mRNA) regulatory network was constructed with Cytoscape 3.7.0. Hub genes were identified with protein interaction (PPI) and validated with the Gene Expression Profiling Interactive Analysis (GEPIA), Human Protein Atlas (HPA) databases, and immunohistochemistry. Survival analyses were also performed using a Kaplan–Meier (KM) plotter. The effects of hsa_circ_0043256 on cell proliferation and cell cycles were evaluated by EdU staining and flow cytometry, respectively. Results hsa_circ_0043256, hsa_circ_0029426 and hsa_circ_0049271 were obtained. Following RT‐qPCR validation, hsa_circ_0043256 was selected for further analysis. In addition, functional experiment results indicated that hsa_circ_0043256 could inhibit cell proliferation and cell‐cycle progression of NSCLC cells in vitro. Prediction by three online databases and combining with DEGs identified from The Cancer Genome Atlas (TCGA), a network containing one circRNAs, three miRNAs, and 209 mRNAs was developed. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated DEGs might be associated with lung cancer onset and progression. A PPI network based on the 209 genes was established, and five hub genes (BIRC5, SHCBP1, CCNA2, SKA3, and GINS1) were determined. Following verification of five hub genes using GEPIA database, HPA database, and immunohistochemistry. High expression of all five hub genes led to poor overall survival. Conclusion Our study constructed a circRNA–miRNA–mRNA network of hsa_circ_0043256. hsa_circ_0043256 may be a potential therapeutic target for lung cancer.